2017
DOI: 10.15446/rsap.v19n2.41332
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo cardiovascular en comunidades urbana y rural: Tinaquillo, Venezuela

Abstract: The results show a high prevalence of cardiovascular risk factors in both communities. Consequently, health promotion programs should reach out to rural communities, as the risk of cardiovascular disease is similar to that of the urban community, who are equally prone to acquire unhealthy habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
2
1
0
1
Order By: Relevance
“…Given the increased CVD morbidity in the rural population, this suggests that these variables used to calculate CVD risk are inadequate in this population sample ( Figure 2 ). This finding is consistent with previous rural versus urban studies done in neighboring Venezuela [ 29 ]. This coupled with the increased burden of disease in the rural population further supports the inadequacy of risk calculators in rural populations in countries like Colombia.…”
Section: Discussionsupporting
confidence: 93%
“…Given the increased CVD morbidity in the rural population, this suggests that these variables used to calculate CVD risk are inadequate in this population sample ( Figure 2 ). This finding is consistent with previous rural versus urban studies done in neighboring Venezuela [ 29 ]. This coupled with the increased burden of disease in the rural population further supports the inadequacy of risk calculators in rural populations in countries like Colombia.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the highest proportion of individuals overweight belong to the urban population. These results coincide with an investigation carried out in Peru where 47.4% and 19.1% of the participants were overweight and obese respectively [ 39 ]; in Mexico, there is a record of 45% obesity in rural areas and 48% in urban areas [ 36 ], and in Venezuela it was evidenced that 60% of both populations are obese and overweight [ 40 ]. This variable is highly influenced by the lifestyle and customs of the two populations.…”
Section: Discussionsupporting
confidence: 88%
“…Respecto a las variables que intervienen en esta problemática, Nuñez-Rocha y cols., 11 identificaron como factor de riesgo cardiovascular más frecuente, el sobrepeso y obesidad en 60% de los casos, valor similar al de otras investigaciones en las que incrementos en el imc son condicionantes de riesgo cardiovascular. 19,23 Esto coincide con lo encontrado en esta investigación. Por ello, las aproximaciones desde el primer nivel de atención, deben estar encaminadas a regular el imc con el fin de evitar complicaciones secundarias que pongan en riesgo la vida de los pacientes.…”
Section: Discussionunclassified